Analisis Hukum Terhadap Urgensi Pendaftaran Merek Bagi Pelaku Usaha Mikro, Kecil, Dan Menengah (UMKM) (STUDI PUTUSAN NOMOR 646 K/Pst.Sus-HKI/2021) - T Fairuz Jasmine (Iuris Studia: Jurnal Kajian Hukum, 2021)
Trademark registration is an important thing that must be done in business, especially micro, small and medium enterprises (MSMEs). One of the reasons is because trademark registration provides legal protection for business actors so that their trademarks are not used by other parties, so that they can anticipate the occurrence of trademark disputes in the future. The urgency of trademark registration for MSME actors is due to the many cases of trademark dispute lawsuits that occur in MSME actors. One example is the case of the “Bodyguard” brand lawsuit. Problems: 1) How is the application of the principle of good faith related to the element of brand passing-off? 2) What is the urgency of trademark registration for Micro, Small and Medium Enterprises (MSMEs)? 3) What are the legal considerations for the judge in the decision regarding the